Geospatial big data and cartography: research challenges and opportunities for making maps that matter - Demšar, U. (2020)
This article presents a new cartographic research agenda focused on making maps that matter using geospatial big data. This agenda provides both long-term challenges that require significant attention and short-term opportunities that we believe could be addressed in more concentrated studies.